The Concept of Fitrah for Children in Ibn Katsir's Qur'an Exegesis: A Pedagogical Implication in Early Childhood Islamic Education - Purnama, Sigit; 'Aziz, Hafidh; Nurhusna, Lu’lu’; Ulfah, Maulidya (Faculty of Tarbiyah and Education, Universitas Islam Negeri (UIN) Sunan Kalijaga Yogyakarta, 2020)
The debate in child development is the factors that influence development, such as genetic factors, heredity, or environmental factors. Filling the room for dialogue and discourse on the conflict of these two causes, Islam offers an alternative to the Qur'an fitrah definition. This study aims to reveal the concept of child fitrah according to Ibn Katsir in the Tafsir Al-Qur'an al-'Aẓhim and the pedagogical implications in early childhood Islamic education. This study uses qualitative research methods with a descriptive-analytic approach. The data were collected through documents and analyzed using the Creswell model analysis technique. The results showed that the concept of human nature (fitrah), according to Ibn Katsir, is based on good innate potential, i.e., Tawheed or religious nature. Therefore, education has to maintain this nature as a positive external agent by referring to Allah's guidance through the Prophet's revelations and examples. It then manifests by observation, literacy, modeling, and reasoning in the learning activity. In the educational process, these efforts can be: 1) Wisdom, which can be interpreted as literacy and modeling. The activities can be memorization and recitation with modeling from adults or teachers; 2) Mau'idhoh, oral transmission method to convey messages, reasoning, and even warnings; 3) If necessary, an excellent Jidal method can be used. Thus, the potential of Fitrah is transformed into a necessity for humans to fulfill their